Living fossil or evolving virus? - Tomonaga, Keizo (Nature Publishing Group, 2010)
Forty million years ago, Bornavirus integrated DNA fragments of itself into the human genome. The modern virus remains strikingly similar to these fragments suggesting that it might preserve the features of the ancestral virus, perhaps even unlocking the secrets of viral origins and evolution.